Altered Cingulum Functioning in Major Depressive Disorder Patient With Suicide Attempts: A Resting-State Functional Magnetic Resonance Imaging Study - Chunxia Yang; Yajuan Duan; Lei Lei; Penghong Liu; Aixia Zhang; Gaizhi Li; Ning Sun; Ning Sun; Yikun Wang; Zhifen Liu; Kerang Zhang (Frontiers in Neuroscience, 2022)
BackgroundMajor depressive disorder (MDD) with suicide attempts (SA) poses a significant public health issue. This study aims to identify neurobiological markers for MDD with SA on resting-state brain functional magnetic resonance imaging (rs-fMRI).MethodsFifty-one unmedicated adult MDD participants, 27 with SA on the Beck Scale for Suicidal Ideation and 24 without SA, underwent rs-fMRI scanning. A group of 30 healthy controls (HC) matched for age, gender, and education-level with MDD were chosen. A whole brain analysis of regional homogeneity (ReHo) was performed on subjects to identify regions where brain activity was associated with SA. Multiple comparison analysis was performed for ReHo. Pearson’s correlation analysis was performed between HAMD-SA scores and ReHo. The statistical significance level was set at p < 0.05.ResultsWe examined whether there were significant differences among the three groups in whole brain ReHo during resting state. Subjects with SA showed significant increase of ReHo in the right Cingulum Post in comparison with those without SA. Subjects with SA showed significant decrease of ReHo in the right Cingulate Gyrus/Precuneus in comparison with HC. The mean ReHo from the significant brain region was associated with HAMD-SA (item 3 of the HAMD) scores (r = 0.349, P = 0.012) but was not associated with HAMD-24 scores.ConclusionThese results indicate that SA is associated with altered resting-state brain activity. The pattern of elevated activity in the cingulum functioning may be related to SA. Identifying cingulum activity associated with SA may help to elucidate its pathogenesis and etiology.